Potential applications for multifunctional microalgae in soil improvement - Song, Xiaotong; Bo, Yahui; Feng, Yanzhang; Tan, Yinghong; Zhou, Chengxu; Yan, Xiaojun; Ruan, Roger; Xu, Qingshan; Cheng, Pengfei (Frontiers in Environmental Science, 2022)
Soil is the basis of agricultural production, and the quality of soil directly affects crop quality and yield. Microalgae can carry out photosynthesis, carbon and nitrogen fixation, and produce large amounts of valuable biomass coupled with wastewater treatment. Also, microalgae can produce plant hormones and other high-value products, which can promote plant growth, improve soil fertility, soil ecological health, and control crop diseases. This research reviews the characteristics of microalgae in improving soil health, discusses the situation of microalgae in controlling soil pollutants, elaborates on the technical application of microalgae in alleviating soil problems, and proposes potential applications of microalgae in ecological environment. Also, resource utilization of multifunctional microalgae is discussed, to provide a theoretical basis for the application of microalgae in soil improvement.